PENGEMBANGAN INSTRUMEN TES TERTULIS DENGAN MODEL INKUIRI TERBIMBING BERBASIS LITERASI SAINS PADA MATERI SISTEM PEREDARAN DARAH PADA MANUSIA BAGI SISWA KELAS VIII SMP - Mughni Hardiyani; Mariani Natalina; Darmadi Darmadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract:This study aimsto determine the quality of the design of written test instruments with a guided inquiry model based on scientific literacy on the material of the circulatory system in humans for eighth grade students of junior high school developed. This research is a Research and Development (R&D) with the stages of analyzing, design, and development, implementation, evaluation. This research is only carried out until the development stage. The analysis, design, development, internal validation and limited trial phase Iphase were carried out in FKIP Biology Education, University of Riau. External validation and limited trials II were conducted at SMP Negeri 4 Pekanbaru. The study was conducted in April-October 2019. Data collection instruments in the form of validation sheets and written test instruments that have been designed. Validation is done to see the validity of the written test instrument developed, while the trial results aim to find out the quality of the questions, the use of language, the level of readability of the questions, reliability, level of difficulty, distinction, and the function of the question deception. The results of the validation of the written test instrument design aspects include material, construction and language of multiple choice questions and the description is very valid with a mean score of 3.41. The validity of the questions was also illustrated from the aspects of guided inquiry with a score of 3.27 in the form of multiple choice questions and a score of 3.21 in the form of description questions, and the aspect of scientific literacy was very valid with a mean score of 3.42 in the form of multiple choice questions and 3.38 in the form of description questions. The written test instrument with a guided inquiry model based on science literacy on the material of the circulatory system in humans for eighth grade students of SMP has been developed in the category of very valid and can be implemented in schools.KeyWords:Test Instruments, Science Literacy, Guided Inquiry Model